Ospitare/Hosting Others: Looking for Traces of Transformation in Adults Through Somatic and Artistic Relational Work - Del Negro, Gaia; Luraschi, Silvia; Delorenzi, Cinzia; El Saadany, Dalia (INSTED: Interdisciplinary Studies in Education & Society, 2022)
We are two researchers, an artist, and a social worker. The article presents two stories from an international research project on experiential translation. Our local contribution in the project consisted of two workshops of multimodal translation (Campbell & Vidal, 2019) of a performance and two poetic texts in a public park; and a final piece of art for a collective public exhibition with all other local teams of researchers and artists. The reflections and creative response produced by two participants - a man, a writer/editor; and a woman, a writer/editor and an architect/performer - particularly struck us. The man was not used to somatic practice in groups, and the woman seemed less used to using words in writing and more used to creating things with others in a relationship. In response to our invitation they produced autobiographical texts, photos of an installation in a natural setting, and an audio of an informal conversation with one of us. We found traces in their material of transformation (Dirkx et al., 2006) in the use of creative languages as a possibility to encounter the others deeply with words, body, gesture, positioning, and movement in space. We present the results of a creative compositional analysis (Formenti, 2018) conducted by meeting in a group and going through moments of individual reflexivity and auto/biographical writing as inquiry (Richardson, 1997) to produce connected knowledge about transformation in adult education. The game we want to play, after a long period of social isolation, is one of mirrors to give us the space to reflect on the desire for a collective human flourishing. Others live in us and enable us to see from those other perspectives (Formenti & West, 2018).